2018
DOI: 10.1158/0008-5472.can-17-1597
|View full text |Cite
|
Sign up to set email alerts
|

Tenascin-C Promotes Tumor Cell Migration and Metastasis through Integrin α9β1–Mediated YAP Inhibition

Abstract: Tenascin-C is an extracellular matrix molecule that drives progression of many types of human cancer but the basis for its actions remain obscure. In this study, we describe a cell-autonomous signaling mechanism explaining how tenascin-C promotes cancer cell migration in the tumor microenvironment. In a murine xenograft model of advanced human osteosarcoma, tenascin-C and its receptor integrin α9β1 were determined to be essential for lung metastasis of tumor cells. We determined that activation of this pathway… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(82 citation statements)
references
References 45 publications
4
76
0
Order By: Relevance
“…Coley and colleagues injected live and killed streptococci to treat patients afflicted with soft tissue and bone tumors with relative success (Decker et al , ). Interestingly, we now know that osteosarcoma cells express cFn isoforms that contain EDA and/or EDB, as well as TnC (Kilian et al , ; ; Sun et al , ). Here we used the osteosarcoma Saos‐2 cells to produce model matrices, containing those FnIII targets and showed that Scl1 promotes GAS colonization and biofilm formation on Saos‐2‐derived matrices.…”
Section: Discussionmentioning
confidence: 99%
“…Coley and colleagues injected live and killed streptococci to treat patients afflicted with soft tissue and bone tumors with relative success (Decker et al , ). Interestingly, we now know that osteosarcoma cells express cFn isoforms that contain EDA and/or EDB, as well as TnC (Kilian et al , ; ; Sun et al , ). Here we used the osteosarcoma Saos‐2 cells to produce model matrices, containing those FnIII targets and showed that Scl1 promotes GAS colonization and biofilm formation on Saos‐2‐derived matrices.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, TNC expression in Ewing sarcoma increases upon microenvironmental stress (hypoxia or nutrient deprivation) [213]. Interestingly, while in osteosarcoma, TNC binding to α9β1 integrin promoted metastasis by repressing YAP nuclear translocation and target gene activation [214], TNC binding to α5β1 integrin in Ewing sarcoma promoted metastasis by activating YAP [207], potentially through activating tyrosine phosphorylation by SRC kinase [213].…”
Section: Yap/taz In Ewing Sarcomamentioning
confidence: 99%
“…While integrating TN-C, it is possible that POSTN could also serve as a scaffold for BMP-1, LOX-1 and collagen to accelerate collagen crosslinking into migratory tracks during metastasis (172). Mechanistically, track mobility involves TN-C competing for syndecan-4 binding to fibronectin, which blocks integrin α5β1mediated cell adhesion for detachment (139), followed by TN-C promotion of migration through integrin α9β1 following YAP inactivation (209). As previously discussed, TN-C and POSTN can bind multiple ECM proteins (i.e.…”
Section: Mcp Influence On the Metastatic Nichementioning
confidence: 99%